Tubble wubble : the clumsy little turtle - Jimenez, Gidget R. (Makati City, Philippines : Tahanan Books, 1998)
Tubble wubble is a turtle who is always in trouble. Why oh why can't he ever do anything right?
Keywords: Turtles--Fiction; Children stories